Enhancement of oxygen diffusion process on a rotating disk electrode for the electro-Fenton degradation of tetracycline. (10th November 2015) - Zhang, Yan; Gao, Ming-Ming; Wang, Xin-Hua; Wang, Shu-Guang; Liu, Rui-Ting
Abstract: An electro-Fenton process was developed for wastewater treatment in which hydrogen peroxide was generated in situ with a rotating graphite disk electrode as cathode. The maximum H2 O2 generation rate for the RDE reached 0.90 mg/L/h/cm 2 under the rotation speed of 400 rpm at pH 3, and −0.8 V vs SCE. The performance of this electro-Fenton reactor was assessed by tetracycline degradation in an aqueous solution. Experimental results showed the rotation of disk cathode resulted in the efficient production of H2 O2 without oxygen aeration, and excellent ability for degrading organic pollutants compared to the electro-Fenton system with fixed cathode. Tetracycline of 50 mg/L was degraded completely within 2 h with the addition of ferrous ion (1.0 mM). The chronoamperometry analysis was employed to investigate the oxygen diffusion on the rotating cathode. The results demonstrated that the diffusion coefficients of dissolved oxygen is 19.45 × 10 −5  cm 2 /s, which is greater than that reported in the literature. Further calculation indicated that oxygen is able to diffuse through the film on the rotating cathode within the contact time in each circle. This study proves that enhancement of oxygen diffusion on RDE is benefit for H2 O2 generation, thus provides a promising method for organic pollutants degradation by the combination of RDE with electro-Fenton reactor and offers a new insight on the oxygen transform process in this new system.